If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 7 = 3x + -53 Reorder the terms: 7 + -12x = 3x + -53 Reorder the terms: 7 + -12x = -53 + 3x Solving 7 + -12x = -53 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -12x + -3x = -53 + 3x + -3x Combine like terms: -12x + -3x = -15x 7 + -15x = -53 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -15x = -53 + 0 7 + -15x = -53 Add '-7' to each side of the equation. 7 + -7 + -15x = -53 + -7 Combine like terms: 7 + -7 = 0 0 + -15x = -53 + -7 -15x = -53 + -7 Combine like terms: -53 + -7 = -60 -15x = -60 Divide each side by '-15'. x = 4 Simplifying x = 4
| 3-6-2= | | 50+65+e=180 | | 3-4(7+9)+6m= | | 65+13t=-0 | | g/-7=-14 | | 2x-3=-x^2+4x+5 | | .6+.8x-4.8=19 | | -10+0.2500d=5 | | -2/5^3 | | -8p-6(6-3p)=5(p-4)-31 | | -10+0.2500d=-5 | | (a+8)(a-9)=0 | | y=-x^2+14x | | (X+2)(3x^2-6x+7)= | | 116+56+v=180 | | -10+0.2500d=0 | | 9x(x+1)=270 | | 2x^3+3x^2-7=0 | | -x+6=2x-9 | | 5/7x=32 | | -6x-16=20 | | 4x^2-4=-32 | | -=q/8-19 | | An=6n+1 | | 2x^2-14x=x+27 | | 4x/3=-3/4 | | 3/4=k(16) | | f(x)=e^3x-1 | | 84+48+2s=180 | | X+x+10+2x-20=180 | | -5+23=68 | | (m+2)=168 |